A multiple-species participatory domestication programme in the Peruvian Amazon: experiences and results to date - Cornelius, J. (2005)
In 1995, the World Agroforestry Centre (ICRAF) and partners initiated a participatory agroforestry domestication programme in the Aguaytía Watershed and Alto Amazonas province of the Peruvian Amazon. The programme, aimed primarily at conservation-through-use of genetic diversity, began with formal, participatory prioritization, leading to selection of four species: bolaina blanca (Guazuma crinita Martius: Sterculiaceae),capirona (Calycophyllum spruceanum (Bentham) Hooker f. Ex Schumann)), guaba (Inga edulis C. Martius: Leguminosae (Mimosoideae)), peach palm (Bactris gasipaes Kunth: Palmae). Open-pollinated seed of each was collected from farmer-selected mother trees, and used in the establishment of a series of seedling seed orchards / progeny tests, the individual blocks of which were dispersed on lands of individual collaborating farmers. Almost ten years later these trials are beginning to produce seed, the Aguaytían famers have organized themselves into a wood and seed producers’ cooperative, the technology developed is being adopted more widely, and genetic results are becoming available. We describe the programme and its results in detail, with special emphasis on its innovative features. Subsequently, we evaluate success to date in relation both to initial objectives and the programme’s response to the evolving local forestry and development environment. Finally, we consider future priorities.